Minipterional Approach for Middle Fossa Skull Base Lesions: Technical Note - Hernandez-Alvarez, V (Thieme Medical Publishers, Inc., 2023)
Surgical access to the middle fossa can be technically challenging. As neurosurgery evolves to minimally invasive approaches, the objective of this study is to demonstrate the extension of the Minipterional approach to access the middle fossa. We present a new surgical approach to the middle fossa for the treatment of secondary trigeminal neuralgia. Three cases are reported to illustrate the following techniques: a patient with petrotentorial meningioma and trigeminal neuralgia, a patient with an arachnoid cyst compressing the fifth nerve, and a patient with a middle cerebral artery aneurysm and a long history of TN (trigeminal neuralgia) refractory to medical and surgical treatments. All three experienced full symptom controls with no permanent neurological deficits. Therefore, the Minipterional technique might represent a feasible, effective, and safe option to treat refractory secondary TN. It also allows approaching these lesions when the posterior fossa approach is compromised by anatomical distortion and enables the simultaneous treatment of secondary trigeminal neuralgia and other lesions, such as aneurysms and meningiomas. © 2023 Thieme Medical Publishers, Inc.. All rights reserved.